EVALUATION OF THE QUALITY CHARACTERISTICS OF COCOA BEAN DRIED USING DIFFERENT DRYING TECHNIQUES - OA, Ogundare; O, Ibitoye; OS, Oyewole; O, Oke; K, Ogungbemi (Innovare Journal of Agricultural Sciences, 2022)
Processing techniques, particularly drying because cocoa beans are extremely sensitive to moisture, have a significant impact on the quality of the final product. Fermented cocoa beans were dried using the NSPRI parabolic solar tent dryer (PSTD), wooden solar dryer (WSD), and open-air drying (OAD). The dried cocoa beans’ respective moisture contents (MCs) for PSTD, WSD, and OAD were 5.94%, 6.01%, and 6.82%, respectively. The corresponding MCs for the dried cocoa beans from PSTD, WSD, and OAD were 5.94%, 6.01%, and 6.82, respectively. It was found that the cut test scores for PSTD, WSD, and OAD were 1000, 985, and 965, respectively. This showed that, in contrast to those from WSD and OAD, the dried cocoa beans obtained from PSTD were fully brown. For WSD, OAD, and PSTD, respectively, the obtained pH values were 5.60, 5.65, and 5.80, and the total titratable acidity was 11.70 meq NaOH 100–1 g, 14.10 meq NaOH 100–1 g, and 18.30 meq NaOH 100–1 g for PSTD, WSD, and OAD, respectively. Food products’ shelf life may be indicated by the titratable acidity value. Due to its enclosed design, the NSPRI PSTD has an advantage over other drying methods because it completely eliminates the possibility of external and microbial contamination of the cocoa beans.